Identification of the causes of convective clouds in extreme rainfall events with hail based on dual-polar radar imagery - Rafi, Rayhan; Kuncoro, Dwi; Arzhida, Bima; Jannah Indriyani, Noor; Warjono, Warjono (Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the atmospheric dynamics behind the formation of convective clouds that produce hail through a multi-instrumental approach. The methods used include streamline map analysis, synoptic data from the Yogyakarta Climatology Station, Himawari-9 HCAI satellite imagery, and dual-polar radar data from the Ahmad Yani Meteorological Station. The results reveal local wind convergence and significant air pressure drop, triggering rapid and intensive formation of Cumulonimbus clouds. Radar products, such as CMAX and HAILSZ, indicate high reflectivity and the presence of large hail particles within the clouds. Hail size is estimated to range from 10–20 mm with a probability of more than 80%. Rain validation shows the highest accumulation of 74 mm/day in Minggir District, Sleman. This study emphasizes the importance of integrating satellite, radar, and surface observation data for detecting extreme weather in tropical regions.